TiO2-Phosphotungstic acid nanocomposites synthesis by annealing method - Milton Praveendaniel; Ponpandian Rajesh Anantha Selvan; Moses Daniel Sweetlin (Next Nanotechnology)
TiO2-Phosphotungstic acid nanocomposites were synthesized by annealing method. In this study, we used a specific annealing technique to optimize the microstructure and improve the performance characteristics of the material under investigation. The chemical nature of the nanocomposites were characterized by UV–visible, Fourier transform infrared (FT-IR), X-ray diffraction (XRD), Energy-dispersive X-ray spectroscopy (EDX), and Scanning electron microscopy (SEM) studies. UV–visible spectroscopy revealed a strong interaction between TiO2 and phosphotungstic acid. FT-IR spectroscopy confirmed new bond formed between TiO2 and phosphotungstic acid in the nanocomposites. XRD showed that the crystallite size of the nanocomposite materials decreased. SEM analysis showed that the particle size decreased and the dopants were uniformly distributed throughout the composite material. The photocatalytic activity of the nanocomposites was evaluated using the pollutant methylene blue dye. The results showed that the nanocomposites had good catalytic activity, with a degradation efficiency of up to 94 %. The temperature-dependent AC and DC electrical conductivities of the composite materials were also studied. The measurements of the dielectric constants produced informative results. Finally, the antimicrobial activities of the nanocomposites were determined by using the agar well diffusion method on the microorganism Streptococcus pyogenes. The results showed that the nanocomposites had a remarkable diameter of the zone of inhibition, indicating their potential as antimicrobial agents. Overall, the synthesized TiO2-phosphotungstic acid nanocomposites have proven to be very promising composites and have wide applications in different fields.